Critical Role for Gi/o-Protein Activity in the Dorsal Striatum in the Reduction of Voluntary Alcohol Intake in C57Bl/6 Mice - Robins, Meridith T.; Chiang, Terrance; Mores, Kendall L.; Alongkronrusmee, Doungkamol; van Rijn, Richard M. (Frontiers in Psychiatry, 2018)
The transition from non-dependent alcohol use to alcohol dependence involves increased activity of the dorsal striatum. Interestingly, the dorsal striatum expresses a large number of inhibitory G-protein coupled receptors (GPCRs), which when activated may inhibit alcohol-induced increased activity and can decrease alcohol consumption. Here, we explore the hypothesis that dorsal striatal Gi/o-protein activation is sufficient to reduce voluntary alcohol intake. Using a voluntary, limited access, 2-bottle choice, drink-in-the-dark model of alcohol (10%) consumption, we validated the importance of Gi/o-signaling in this region by locally expressing neuron-specific, adeno-associated-virus encoded Gi/o-coupled muscarinic M4 DREADDs (Designer Receptors Exclusively Activated by Designer Drug) in the dorsal striatum and observed a decrease in alcohol intake upon DREADD activation. We validated our findings by activating Gi/o-coupled delta-opioid receptors, which are natively expressed in the dorsal striatum, using either a G-protein biased agonist or a β-arrestin biased agonist. Local infusion of TAN-67, an in vitro-determined Gi/o-protein biased delta-opioid receptor agonist, decreased voluntary alcohol intake in wild-type and β-arrestin-2 KO mice. SNC80, a β-arrestin-2 biased delta-opioid receptor agonist, increased alcohol intake in wild-type mice; however, SNC80 decreased alcohol intake in β-arrestin-2 KO mice, thus resulting in a behavioral outcome generally observed for Gi/o-biased agonists and suggesting that β-arrestin recruitment is required for SNC80-increased alcohol intake. Overall, these results suggest that activation Gi/o-coupled GPCRs expressed in the dorsal striatum, such as the delta-opioid receptor, by G-protein biased agonists may be a potential strategy to decrease voluntary alcohol consumption and β-arrestin recruitment is to be avoided.